BAHAN AJAR BERBANTUAN SMART APPS CREATOR UNTUK PENINGKATAN HASIL BELAJAR PESERTA DIDIK - Lestari, Eva; Hidayati, Siti Nurul (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This study aims to describe learning outcomes, and student responses during learning using teaching materials assisted by smart apps creator (SAC). This type of research uses pre-experimental research with a one group pretest posttest design. The subjects of this study consisted of 30 students of class VIII-H at SMP Negeri 30 Surabaya in the academic year 2022/2023. The research instruments used were pretest-posttest test sheets and student response questionnaires. The data collection techniques used were tests and questionnaires, with data analysis techniques including data analysis techniques for improving learning outcomes using normalized gain (N-gain) and analyzing student response questionnaire data. The results of this study include, (1) the learning outcomes of students experienced a significant increase as evidenced by the average value of normalized gain (N-gain) obtained a high category, (2) the results of students' responses obtained an average percentage of 98.5% with a very good category. Based on the results of the research conducted, it can be concluded that the application of teaching materials assisted by Smart Apps Creator (SAC) can improve student learning outcomes on vibration and wave material.